2015
DOI: 10.1111/ajag.12232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Zealand program to improve transition of care for older high risk adults

Abstract: Transition interventions aim to improve care and reduce hospital readmissions but evaluations of these interventions have reported inconsistent results. We report on the evaluation of an intervention implemented in Auckland, New Zealand. Participants were people over the age of 65 who had an acute medical admission and were at high risk of readmission. The intervention included an improved discharge process and nurse telephone follow-up soon after discharge. Outcomes were 28 day readmission rates and emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 17 publications
0
21
0
3
Order By: Relevance
“…Five studies were RCTs, eight were quasi-experiments (four prospective controlled pre–post design and one retrospective controlled pre–post design) and three were retrospective non-controlled observational studies. Four interventions took place in the USA,14–17 while two interventions were set in the UK,18 19 New Zealand20 21 and Singapore 22 23. Additionally, there was one intervention each in France,24 Australia,25 Denmark,26 Mexico27 and Hong Kong 28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were RCTs, eight were quasi-experiments (four prospective controlled pre–post design and one retrospective controlled pre–post design) and three were retrospective non-controlled observational studies. Four interventions took place in the USA,14–17 while two interventions were set in the UK,18 19 New Zealand20 21 and Singapore 22 23. Additionally, there was one intervention each in France,24 Australia,25 Denmark,26 Mexico27 and Hong Kong 28.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCT studies were considered as presenting low risk of bias,20 26 while the others presented an unclear risk of bias due selective reporting that was discordant with the protocol,25 due to implementation problems and power analysis18 and due to the randomisation process 15. Two quasi-experimental studies presented low risk of bias,17 21 while the others were assessed as showing unclear risks due to a lack of randomisation15 24 27 and programme implementation issues 21. The remaining studies presented a high risk of bias due to elements of the methodological design or analysis16 19 22 23 28 and baseline differences 14 27.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first study looking at telephone follow‐up of a group of frail older people after specialist geriatric care, whether as a single phone call or multiple calls over a longer period. Other studies have looked at earlier one‐off telephone interventions (two to three days) , shorter follow‐up (30 days) , younger patients , postacute care or surgical care , a single discipline intervention (such as pharmacy) or multiple interventions with telephone calls as just one part of a larger intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using telephone follow‐up in the first three days after discharge have found high levels of unmet needs , but the intervention has had mixed results, with a reduction or no reduction in readmissions. Likewise, studies where the intervention commenced a longer period after discharge have had conflicting results for the effectiveness of telephone follow‐up in reducing readmissions .…”
Section: Introductionmentioning
confidence: 99%
“…Revisit rates are often considered a proxy measure to reflect the quality of care transitions, but considering the results of the current larger scaled study, evidence remains limited that telephonic programs affect healthcare use. When evaluating the effect of telephone support programs after ED or even hospital discharge, most have found no differences in outcomes of readmission rates or ED use . Some telephone follow‐up programs have demonstrated incremental improvement in process measures such as better follow‐up appointment rates but little to no effect on hospital use .…”
mentioning
confidence: 99%